2011
DOI: 10.4103/2230-973x.82423
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development and in vitro evaluation of gastroretentive hollow microspheres of famotidine

Abstract: Background:The main aim of this study was to develop a gastroretentive, multiple-unit floating drug delivery system for a drug which is poorly absorbed from the lower gastrointestinal tract. Such a dosage form may provide an extended retention of drug in the upper gastrointestinal tract resulting in enhanced absorption and improved bioavailability.Materials and Methods:Microspheres were prepared by the emulsion solvent diffusion method. Four different ratios (1:1, 1:2, 1:3, and 1:4) from each polymer, i.e., Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is likely that the 365 highly water-soluble drug has escaped the insoluble macromolec-366 ular matrix of Eudragit RL. Previous reports indicated that drug 367 release from Eudragit RL matrix is governed by diffusion mecha-368 nism[30][31][32][33]. Faster release pattern is demonstrated in smaller 369 size tablets (60 mg and 120 mg) compared to that of larger ones, 370 e.g.…”
mentioning
confidence: 98%
“…It is likely that the 365 highly water-soluble drug has escaped the insoluble macromolec-366 ular matrix of Eudragit RL. Previous reports indicated that drug 367 release from Eudragit RL matrix is governed by diffusion mecha-368 nism[30][31][32][33]. Faster release pattern is demonstrated in smaller 369 size tablets (60 mg and 120 mg) compared to that of larger ones, 370 e.g.…”
mentioning
confidence: 98%
“…The investigated formulation was a simple two-component system with an 80% mass loading of Eudragit RL PO and a 20% mass loading of famotidine. Importantly, famotidine is known to be prone to degradation right after melting ( Chordiya et al, 2011 ; Maniruzzaman et al, 2013 ; Mustafin, 2011 ; Parikh et al, 2014 ; Perpétuo et al, 2013 ; Viciosa et al, 2016 ). Hence, API degradation was expected during extrusion and was used as a quality attribute.…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that the two components do not interact with each other ( Chordiya et al 2011 ). They are suitable candidates for the preparation of solid dispersions since the melting point of Famotidine (form B, 166°) and the expected extrusion temperature window of Eudragit RL (165–170 °C) ( Parikh et al 2014 ) are within a similar temperature range.…”
Section: Methodsmentioning
confidence: 99%